An efficiency-based capacity formulation: mathematical properties and practical implications. Issue 4 (10th December 2021) - Shao, Changqiao; Siam, M. R. K.; Deng, Shejun; Wang, Yong; Wang, Haizhong
Abstract : Traditional capacity approaches focus only on the vehicle-carrying ability of a facility; i.e. a freeway segment is characterized by higher speed and volume. Furthermore, these definitions lead to the two-capacity phenomenon which creates confusion among practitioners and researchers over which one is the appropriate value. To address these issues, this paper puts forth a new understanding of freeway capacity by considering the optimal traffic state idea where the infrastructure is operating in the most efficient way. This paper endeavors to explain the existence of the optimal traffic state that may lead to a substantial amelioration of traffic conditions on freeways. These analytical properties are transferable to different families of speed–density models. A simulation study is then undertaken to demonstrate how additional benefits can be achieved using the efficiency-based approach. Results show that the proposed methodology improves the overall traffic network performance in comparison to when conventional capacity is used.